Effect of proinflammatory interleukins on jejunal nutrient transport. (1st August 2000) - Hardin, J; Kroeker, K; Chung, B; Gall, D G
Abstract : AIM: We examined the effect of proinflammatory and anti-inflammatory interleukins on jejunal nutrient transport and expression of the sodium-glucose linked cotransporter (SGLT-1). METHODS: 3- O -methyl glucose and l -proline transport rates were examined in New Zealand White rabbit stripped, short circuited jejunal tissue. The effects of the proinflammatory cytokines interleukin (IL)-1α, IL-6, and IL-8, IL-1α plus the specific IL-1 antagonist, IL-1ra, and the anti-inflammatory cytokine IL-10 were investigated. In separate experiments, passive tissue permeability was assessed and brush border SGLT-1 expression was measured by western blot in tissues exposed to proinflammatory interleukins. RESULTS: The proinflammatory interleukins IL-6, IL-1α, and IL-8 significantly increased glucose absorption compared with control levels. This increase in glucose absorption was due to an increase in mucosal to serosal flux. IL-1α and IL-8 also significantly increasedl -proline absorption due to an increase in absorptive flux. The anti-inflammatory IL-10 had no effect on glucose transport. The receptor antagonist IL-1ra blocked the ability of IL-1α to stimulate glucose transport. IL-8 had no effect on passive tissue permeability. SGLT-1 content did not differ in brush border membrane vesicles (BBMV) from control or interleukin treated tissue. CONCLUSIONS: These findings suggest that intestinal inflammation and release of inflammatory mediators such as interleukins increase nutrient absorption in the gut. The increase in glucose transport does not appear to be due to changes in BBMV SGLT-1 content.